Effects of aerobic dance on systolic blood pressure in stage one hypertensive adults in Uganda - Nahwera, Loyce; Kiptolo Boit, Edwin; Nsibambi, Constance A.N.; Maghanga, Mshilla; Wachira, Lucy-Joy (BMJ Publishing Group Ltd, 2025)
Objective. To investigate the effects of a 12-week aerobic dance programme on systolic blood pressure (SBP) in stage one hypertensive adults. Methods. This study employed an experimental research design. 36 out of 58 stage one hypertensive adults randomly assigned into experimental and control groups completed the programme. SBP was measured using a mercury sphygmomanometer at baseline and post programme. The experimental group participants trained thrice a week, 45 min per session, and at a moderate intensity, but the control group continued doing their daily routines. Data were analysed using SPSS V.20. A two-tailed t-test was used to compare the mean differences of the two groups. A p value of <0.05 was considered statistically significant. Results. The experimental group had a mean SBP of 143.83±6.382 mm Hg at baseline, while the control had 137.61±6.400 mm Hg. After a 12-week aerobic dance programme, the mean SBP of the experimental group reduced to 136.33±9.191 mm Hg, while that of the control group increased to 139.56±9.954 mm Hg. This implies that the 12-week aerobic dance programme reduced the SBP of the experimental group by −7.50 mm Hg while that of the control group remained more or less the same by having a marginal increment of 1.50 mm Hg. The changes were statistically significant (p<0.002) after a 12-week aerobic dance programme. Conclusion. The aerobic dance programme effectively manages the SBP of stage one hypertensive adults. In Uganda, stakeholders and policymakers should consider incorporating aerobic dance as a non-pharmacological method for hypertension management protocols.